2022
DOI: 10.36103/ijas.v53i3.1572
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Docking Karadi Lambs on Growth Performance, Carcass Traits and Body Composition

Abstract: Twelve new born Karadi lambs were docked within 3 days of their birth using rubber-rings, and left with their mothers till weaning (2.5 months). Another 12 weaned Karadi lambs obtained from local market were left intact. Following an adaptation period of a week, the docked and intact lambs with an average initial weight of 16.83±1.522 and 19.92± 0.748kg were randomly divided into three equal groups to be slaughtered at 20, 30 and 40kg. Results revealed that overall means of daily gain in weight, dressing perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…The allometric growth coefficient of leg weight is differ between treatments in relation to half carcass weight, while it was found that the b value in docked lambs is near to one (1.036), which means isogonic growth and grew at a similar rate to carcass weight, on the other hand, the b value in intact lambs was (0.845), indicating low impetus and early maturing cut and the growth rate was lower than that of carcass weight. Such difference could be attributed to more deposition of fat in the leg of docked lambs compared to intact lambs (20.18 vs. 12.99%) (8). This result for intact lambs are in accordance with Alvarez-Rodriguez, et al, (9) who indicated that the allometric growth of leg cuts in relation to half carcass weight was an early developed.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The allometric growth coefficient of leg weight is differ between treatments in relation to half carcass weight, while it was found that the b value in docked lambs is near to one (1.036), which means isogonic growth and grew at a similar rate to carcass weight, on the other hand, the b value in intact lambs was (0.845), indicating low impetus and early maturing cut and the growth rate was lower than that of carcass weight. Such difference could be attributed to more deposition of fat in the leg of docked lambs compared to intact lambs (20.18 vs. 12.99%) (8). This result for intact lambs are in accordance with Alvarez-Rodriguez, et al, (9) who indicated that the allometric growth of leg cuts in relation to half carcass weight was an early developed.…”
Section: Resultssupporting
confidence: 79%
“…After an adaptation period of a week, the docked and intact lambs with an average initial weight of 16.83± and 19.92± kg respectively, were randomly divided into three equal groups to be slaughtered at 20, 30 and 40kg, and each group was housed in a separate pen and fed a pelleted diet containing 16% crude protein and 2769 Kcal energy and straw ad libitum. Full details of the experiment are described in our previous paper (8) Slaughtering of the animals When each lamb reached its desired slaughter weight (20, 30 and 40 kg), they were slaughtered after fasting for 12 hours, with unlimited access to water. The lambs were slaughtered at abattoir according to Islamic method, by severing the necks and major blood vessels.…”
Section: Animal and Experimental Designmentioning
confidence: 99%